Design and Realization of File System Based on NAND Flash Chips - LI Xiaotao; YI Hong; HE Jianguo (机车电传动)
A file system design based on storage space pre-distributing and redundant data management using by NAND Flash chips was introduced, which could access large bulk of data and satisfied the data available and recoverable requirement.